Pengaruh Pertumbuhan Ekonomi, PAD, DAU dan DAK Terhadap Pengalokasian Anggaran Belanja Modal di Kabupaten/Kota Di Sumatera Utara Tahun 2018-2020 - Herlina Novita; Anita Yuli Sari Akbar Purba; Erika Sri Dwina Br Perangin-Angin; Engie Aurel Caroline; Julius Kristofan Zai (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this research is to investigate the impact of economic growth, regional original income, general allocation funds, and special allocation funds on the distribution of capital expenditure funds in the regencies and cities of North Sumatra, Indonesia. Purposive sampling was used to pick the samples for this study. Three hundred and ninety-nine samples were included in the study, all of which were from districts or cities in North Sumatra. Statistical analysis, classical assumption testing, and hypothesis testing are the research approaches that were used in this thesis. Secondary data is the kind of information that was utilized. In this research, the findings demonstrate that economic growth, regional original income, general allocation funds, and special distribution funding all have a positive and statistically significant impact on capital expenditures. A partial influence of regional original income and special allocation funds on capital expenditures may be seen, but no effect is shown for economic growth and general allocation funds on capital expenditures